Effect of Pure and Mixed Plantations of Populus deltoides with Alnus subcordata on Growth, Nutrition and Soil Properties - Abdollah Mousavi Koupar, Seyed; Mohsen Hosseini, Seyed; Modirrahmati, Alireza; Tabari, Masoud; Golchin, Ahmad; Hosseinzadeh Rad, Farzam (Asian Journal of Chemistry, 2010)
Plantation and application of fast-growing species such as Populus deltoides are increasingly in the north of Iran.Concerns about decline in soil fertility and long-term productivity of fastgrowing plantations have promoted interest in using nitrogen-fixing trees in mixed species plantations. Populus deltoides and Alnus subcordata were planted in five proportions (100P, 70P:30A, 50P:50A, 30P:70A, 100A) in Astaneh, Iran. After 12 years, the effects of species interactions on tree growth and nutrient concentration in live and senescent leaves and soil properties were assessed. Diameter at breast height and total height of individual Populus deltoides trees were positively affected by the presence of Alnus. Nitrogen concentrations in fully expanded and senescent leaves of Populus deltoides were higher in mixed plantations than monoculture plantations. The results of nutrition and nutrient return and growth indicated that mixed plantations of these two species were more productive and sustainable than their monoculture plantations. Within the framework of this experiment, it appeared that production was maximized when these two species were grown together in the relative proportions of 30 % Populus deltoides and 70 % Alnus subcordata.